2022
DOI: 10.3389/fonc.2022.864106
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of Five Rare Pathological Subtypes of Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a highly heterogeneous tumor with several rare pathological subtypes and which is still poorly understood. This study aimed to describe the epidemiological and clinical spectrum of five rare HCC subtypes and develop a competing risk nomogram for cancer-specific survival prediction.MethodsThe study cohort was recruited from the Surveillance, Epidemiology, and End Results database. The clinicopathological data of 50,218 patients histologically diagnosed with classic HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Chen XY et al. reported that the median cancer-specific survival times of the classic HCC and rare S-HCC were comparable at 15 and 13 months, respectively ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen XY et al. reported that the median cancer-specific survival times of the classic HCC and rare S-HCC were comparable at 15 and 13 months, respectively ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model was highly reliable, with a consistency index of 0.781 in the training cohort and 0.793 in the verification cohort. The model is a new approach that can be extended to clinical practice and guide individualized therapy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the global cancer statistics report, there will be about 840,000 new cases of hepatocellular carcinoma worldwide in 2020, and about 780,000 new deaths worldwide [ 1 ]. Data from a national survey in the United States showed that in 2022, liver cancer related deaths in males and females ranked the 7th and 5th among all malignant tumors, while studies in China showed that liver cancer ranked the first among all malignant tumors in disability-adjusted years [ 2 7 ]. In 2014, a survey data released by the World Health Organization showed that the prevalence rate of hepatitis B surface antigen in the general population in China was about 5.49%, and there were about 74 million cases of hepatitis B carriers in China.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcomatous variants of carcinomas have been described in many cancer types, including the liver, even more frequently in hepatocellular carcinoma than in biliary tract carcinoma (Chen et al, 2022). Sarcomatous cholangiocarcinoma (SICC) represents about 4.5 % of intrahepatic cholangiocarcinomas (Zhang et al, 2018b) and is more common in Asian Countries (Boonsinsukh et al, 2018).…”
Section: Epidemiologymentioning
confidence: 99%